On the Role of Dietary Nitrate in the Maintenance of Systemic and Oral Health - Ulrich Schlagenhauf (MDPI AG, 2022)
The assessment of the significance of nitrates ingested with food has undergone a fundamental change in recent years after many controversial discussions. While for a long time, a diet as low in nitrates as possible was advocated on the basis of epidemiological data suggesting a cancer-promoting effect of nitrate-rich diets, more recent findings show that dietary nitrate, after its conversion to nitrite by nitrate-reducing bacteria of the oral microbiota, is an indispensable alternative source for the formation of nitric oxide (NO), which comprises a key element in the physiology of a variety of central body functions such as blood pressure control, defense against invading bacteria and maintenance of a eubiotic microbiota in the gut and oral cavity. This compact narrative review aims to present the evidence supported by clinical and in vitro studies on the ambivalent nature of dietary nitrates for general and oral health and to explain how the targeted adjuvant use of nitrate-rich diets could open new opportunities for a more cause-related control of caries and periodontal disease.